A comparison of micrometeorological methods for marine roughness estimation at a coastal area. Issue 195 (December 2019) - He, Y.C.; Fu, J.Y.; Shu, Z.R.; Chan, P.W.; Wu, J.R.; Li, Q.S.
Abstract: Marine roughness length z0 is an essential parameter for the parameterization of momentum flux exchanges at sea-atmosphere interface. This paper aims to examine the performance of four widely adopted micrometeorological methods and four direct modeling methods, for estimating marine surface roughness at a coastal area. Comparative analyses are carried out based on four-year measurements from an offshore platform that was equipped with LiDAR profiler, meteorological mast and other hydrologic measurement devices. The analyzed results show that the marine roughness length scales estimated via the profile method and the gust-factor method are unrealistically small, generally one or two orders of magnitude smaller than those predicted via the direct modeling methods. By contrast, both the speed-variance and direction-variance methods can provide more reasonable estimation results that compares favorably with those predicted by the direct modeling methods. It is also observed from the results that the features of waves in this shallow-water area differ from those at deep waters, including the independence of significant wave period upon wind speed and the less correlation between wave and wind directions. Based on the collected wave records, a modified empirical model of marine roughness is presented. Highlights: Analyse 4-year records from LiDAR profiler, anemometer and hydrologic measurement devices. Compare 4 micrometeorological methods and 4 direct modeling methods for estimating marine roughness z0 . Observe overly-underestimated z0 via profile and gust-factor methods compared to that via direct modeling methods. Propose a modified wave model (i.e., z 0 = 1200 H s ( H s / L p ) 5, L p = g T p 2 / ( 2 π ) ) for quantifying z0 .